Accommodation and sediment‐supply controls on clastic parasequences: A meta‐analysis. Issue 4 (15th April 2020) - Colombera, Luca; Mountney, Nigel P.
Abstract: This study combines data from many published case studies to undertake a quantitative characterization of clastic parasequences, with the aim to determine how accommodation, sediment supply and autogenic sediment‐storage dynamics are recorded in their sedimentary architecture and stacking patterns. Results of this study are used to critically evaluate the validity of paradigms and models that are routinely used to explain and predict trends in the anatomy and arrangement of parasequences. Data on 957 parasequences from 62 case studies of clastic, shallow‐water successions were coded in a relational database, which includes outcrop and subsurface datasets of ancient and Quaternary examples. These units cover the preserved records of both river‐dominated deltas and wave‐dominated coasts, representing shoreline transits over a breadth of timescales, likely of both local and regional extent. The role of extant accommodation, rates of creation of accommodation and rates of sediment supply in determining parasequence architecture is assessed through analysis of relationships between: (i) proxies of these variables at different scales (rates of aggradation and progradation, facies‐belt shoreline trajectories, systems‐tract type, parasequence‐set stacking patterns, parasequence progradation angle and stratigraphic rise, size of feeder rivers); and (ii) parameters that describe the geometry and stacking style of parasequences, and associated shallow‐water sand bodies. Statistical analyses of database outputs indicate which proxies of accommodation, sediment supply and accommodation/sediment‐supply ratio are significant as predictors of parasequence architecture, and allow for interpretations of the importance of allogenic and autogenic factors. The principal results of this study reveal the following: (i) parasequence thickness varies as a function of water depth, accommodation generation and erosional truncation, and these variations are also reflected across types of systems tracts and parasequence sets; (ii) the dip length of parasequence sand bodies demonstrates scaling with measures of accommodation/sediment‐supply ratio at multiple scales, partly in relation to the possible effect of sediment supply on progradation rates; (iii) in systems tracts, stratigraphic trends in parasequence stacking due to autogenic mechanisms or to acceleration or deceleration in relative sea‐level fluctuations are not revealed quantitatively; (iv) some association is seen between the abundance of deltaic or river‐dominated parasequences and progradational stacking; (v) positive but modest correlation is observed between measures of river‐system size and the dip length of shallow‐marine parasequence sand bodies. The resulting insights can be applied to guide sequence stratigraphic interpretations of the rock record and the characterization of sub‐seismic stratigraphic architectures of subsurface successions.